Effects of TI and Sr site substitutions on superconductivity, structure and excess conductivity of TISr2CaCu2O7-δ ceramics / Nurulhuda Ahmad - Ahmad, Nurulhuda (2010)
The study involves four different compounds ofT1Sr1212 superconductors. There are T11-xCuxSr1.8Yb0.2CaCu2O7-δ (x=0.0-0.6), T11-xCuxSr1.6Yb0.4CaCu2O7-δ (x=0-0.5), T10.5Pb0.5Sr2-xMgx Ca0.8Yb0.2Cu2O7-δ (x=0-1.0) and T10.5Pb0.5Sr2-xYbxCaCu2O7-δ (x = 0.1-0.4) series. All the samples were synthesized using the solid state synthesis method. Temperature dependent electrical resistance measurements on T11-xCuxSr1.8Yb0.2CaCu2O7-δ (x = 0.006) series showed the best superconducting behavior at x=O.4 with zero resistance critical temperature (TC zero) of 77.6 K. On the other hand, electrical resistance measurements on T11-xCuxSr1.6Yb0.4CaCu2O7-δ (x=0-0.5) series showed gradual decrease in TC zero followed by a sudden increase in TC at x = 0.3. Further substitution of Cu at x≥0.4 however caused TC to be suppressed. Electrical resistance measurement in T10.5Pb0.5Sr2-xMgxCa0.8Yb 0.2Cu2O7-δ (x=0-1.0) showed increasing semiconductor-like normal state behavior and gradual suppression of Tc with Mg. In addition, superconducting fluctuation behavior (SFB) in T11-xCuxSr1.8Yb0.2CaCu2O7-δ (x=0.0-0.4), T11-xCuxSr1.6Yb0.4CaCu2O7-δ (x=0-0.3), T10.5Pb0.5Sr2-xMgxCa0.8Yb0.2Cu2O7-δ (x=0) and T10.5Pb0.5Sr2-xYbxCaCu2O7-δ (x= 0.1-0.4) ceramics were analyzed by using Asmalazov-Larkin (AL) theory as a framework. In T11-xCuxSr1.8Yb0.2CaCu2O7-δ (x=0-0.4), the analysis showed characteristic cross-over from 2D to 3D behavior with decreasing temperature. Cu substitutions in this series is suggested to give effect on c-axis coherence length, ξC(0) and hole concentration of carrier. For T11-xCuxSr1.6Yb0.4CaCu2O7-δ (x=0-0.3) ceramics revealed 2D to 3D transition and showed Cu substitution affects the AL3D constant and increases c-axis coherence length, ξC(0) . Excess conductivity of T10.5Pb0.5Sr2-xMgxCa0.8Yb0.2Cu2O7-δ ceramics (x=0.0) showed exclusively 1D to 2D transition behavior. In addition, superconducting fluctuation behavior in sintered polycrystalline samples of T10.5Pb0.5Sr2-xYbxCaCu2O7-δ (x=0.1-0.4) revealed transition from 2-D to 3-D behavior. This study also suggests that there is a close correlation between the amounts of Yb substitution and the behavior of AL constant (A). Fourier Transform Infrared (FTIR) spectroscopy analyses was performed on T11-xCuxSr1.6Yb0.4CaCu2O7-δ (x=0-0.5) and T10.5Pb0.5Sr2-xMgxCa0.8Yb0.2Cu2O7-δ (x=0-1.0) samples. In T11-xCuxSr1.6Yb0.4CaCu2O7-δ (x=0-0.5), the results showed CuO2 planar oxygen mode observed was softened with increased Cu substitution indicating enhanced coupling between CuO2 planes. FTIR absorption data for T10.5Pb0.5Sr2-xMgxCa0.8Yb0.2Cu2O7-δ (x=0-1.0) indicate possible tilt of oxygen atoms in the CuO2 plane as a result of unequal bond lengths and enhanced CuO2 inter-plane coupling.